Magnetic Surface Molecularly Imprinted Polymer for Selective Adsorption of 4-Hydroxycoumarin - Kuang, Yi; Xia, Yunlong; Wang, Xing; Rao, Qingqing; Yang, Shengxiang (Frontiers in Chemistry, 2022)
4-hydroxyl coumarin (HC), an important intermediate during the synthesis procedure of rodenticide and anti-cardiovascular drug, shows highly medicinal value and economic value. To achieve the efficient adsorption of HC from natural biological samples, a novel magnetic surface molecularly imprinted polymer (HC/SMIPs) was constructed by employing methacrylic acid (MAA) as functional monomer, organic silane modified magnetic particles as matrix carrier and HC as template molecule. Due to the numerous specific imprinted cavities on the HC/SMIPs, the maximum adsorption capacity of HC/SMIPs for 4-hydroxycoumarin could reach to 22.78 mg·g-1 within 20 min. In addition, HC/SMIPs exhibited highly selective adsorption for 4-hydroxycoumarin compared with other active drug molecules (osthole and rutin) and showed excellent regeneration performance. After 8 cycles of adsorption-desorption tests, the adsorption capacity of HC/SMIPs just slightly decreased by 6.64%. The efficient selective removal and easy recycle of 4-hydroxycoumarin from biological samples by HC/SMIPs made a highly promising to advance the application of imprinting polymers in complex practical environments.